Discrimination of Vitis vinifera varieties using DNA fingerprinting and NMR coupled with chemometrics and their impact on the efficacy of fluoxetine and indomethacin in vivo. Issue 6 (7th April 2021) - Youssef, Fadia S.; Labib, Rola M.; Sleem, Amany A.; Meselhy, Khaled M.
Abstract: The grapes, Vitis vinifera, belong to family Vitaceae. Some fruit juices substantially decrease the oral absorption of certain drugs undergoing intestinal uptake transport. Green seedless "Thompson" type (GT) and reddish black seeded "Magic black" type (BM) of V. vinifera L. were discriminated using deoxyribonucleic acid (DNA) fingerprinting and nuclear magnetic resonance (NMR) coupled with chemometrics. Their effects on the bioavailability of fluoxetine and indomethacin were assessed in vivo. Practical applications: Random amplification of polymorphic DNA (RAPD) analysis of GT and BM revealed that primers OPA‐02 and OPB‐10 indicate a taxonomical relationship between them as they produced high similarity coefficients estimated by 80 and 66.67%, respectively. OPC‐03, OPB‐13, and OPC‐07 primers help in their discrimination based on their minimal levels of similarity coefficients estimated by zero percentages accompanied by the high levels of polymorphism. Principal component analysis score plot obtained from processing of proton nuclear magnetic resonance ( 1 H NMR) showed very good discrimination between GT and BM in PC1 that accounts for most of the variance. Oral administration of 100 mg/kg of GT and BM separately produce no significant change in immobility period of rats dropped individually into a glass cylinder. Concomitant administration of either 100 mg/kg of GT or BM with 20 mg/kg of fluoxetine significantly decreased the efficacy of antidepressant reference drug (fluoxetine) by decreasing time before immobility showing a percentage of depression inhibition estimated by 17.2 and 29.1%, respectively, that obviously decreased when compared to fluoxetine alone. Regarding anti‐inflammatory activity, both GT and BM exhibited a notable activity by inhibiting the increase in paw edema and inflammation induced by carrageen in rats where BM is more potent approaching indomethacin. Administration of GT or BM with indomethacin reduces its efficacy revealing 27.5 and 26.1% in edema percentage after 1 hr, respectively, that decreased minimally to be 19.1% and 15.6% after 4 hr, respectively, instead of 7% in case of indomethacin alone. Thus, it can be concluded that DNA and NMR fingerprinting could successfully differentiate between Vitis varieties. Grape juice decreased the efficacy of fluoxetine and indomethacin. Further studies should be conducted to declare the effect of Vitis varieties on the bioavailability of additional drugs that treat chronic diseases as diabetes and hypertension.